Basic program analyses fluid rheology to determine pump rates - MOFTAH, K. R (The Oil & gas journal, 1994)
The use of statistical methods can improve the selection of a rheological model and the subsequent calculations for critical pump rate and pressure drop for cementing operations. The accompanying interactive Basic computer program allows the user to analyze fluid rheology to help determine the best data for use in predicting cementing pump rates. An accurate critical pump rate and pressure drop can then be calculated based on the correctly calculated rheological parameters. For cementing operations, the important methods of calculating the critical pump rate are the Hedstrom analysis, based on the Bingham plastic rheological model, and the Metzner and Reed analysis, based on the power law rheological model.